Regulation of STIM1/Orai1-dependent Ca2+ signalling in platelets - Lang, F; Münzer, P; Gawaz, M; Borst, O (Thrombosis and haemostasis, 2013)
Platelet secretion and aggregation as well as thrombus formation of blood platelets critically depend on increase of cytosolic Ca2+ concentration ([Ca2+]i) mainly resulting from intracellular Ca2+ release followed by store operated Ca2+ entry (SOCE) through Ca2+ release activated channels (CRAC). SOCE is in part accomplished by the pore forming unit Orai and its regulator stromal interaction molecule (STIM). Orai1 and STIM1 transcription is stimulated by NF-κB (nuclear factor kappa B). Serum- and glucocorticoid-inducible kinase 1 (SGK1) up-regulates NF-κB-activity in megakaryocytes and thus Orai1-expression and SOCE in platelets. SGK1 is thus a powerful regulator of platelet Ca2+-signalling and thrombus formation and presumably participates in the regulation of platelet activation by a variety of hormones as well as clinical conditions (e.g. type 2 diabetes or metabolic syndrome) associated with platelet hyperaggregability and increased risk of thromboocclusive events. SOCE in platelets is further regulated by scaffolding protein Homer and chaperone protein cyclophilin A (CyPA). Additional potential regulators of Orai1/STIM1 and thus SOCE in platelets include AMP activated kinase (AMPK), protein kinase A (PKA), reactive oxygen species, lipid rafts, pH and mitochondrial Ca2+ buffering. Future studies are required defining the significance of those mechanisms for platelet Orai1 abundance and function, for SOCE into platelets and for platelet function in cardiovascular diseases.